LABORATORY STUDIES ON NEEM KERNELS AND LEAVES AS WHEAT PROTECTANTS (Biological Sciences - PJSIR, 2002)
The extracts of neem seed kernels and leaves and their powders were tested  for the repellent  and antifeedant  activities  against Tribolium castaneum (Herbst)  and  Rhizopertha  dominica  (Fabricius)  respectively.  The  best  repellent  activity  class (iv) was observed in fresh seed kernels extracted in ethyl alcohol at 150 mg cm2 . Whereas the benzene, hexane and acetone extracts of the seed kernels were not effective at the same dose. Dry powder of fresh seed kernels protected wheat  from  infestation  upto  one year  at  higher dose.